Zimbabwe’s Housing Shortage: Murambatsvina and Small-Scale Landlordism - Mhlahlo, Samson R. (Peter Lang AG, 2021)
When white colonial governance ended and ushered in a black political dispensation in April 1980, all legal and institutional constraints on movements to towns and cities no longer applied. Subsequently, the country experienced rapid urban migration and growth in the context of relative post-independence prosperity. Despite such developments, however, the Zimbabwe government and its urban municipalities continued to adhere to pre-independence housing policies. These made it both increasingly difficult and expensive for low-income urban residents to access and comply with legal housing requirements. The housing shortage and its twin seed, small-scale landlordism was thus planted.